NUMERICAL AND EXPERIMENTAL STUDY OF A TWO-STAGE SAVONIUS WIND TURBINE - Kothe, L. B.; Petry, A. P. (Revista de Engenharia Térmica, 2019)
This article presents a numerical and experimental study of vertical axis wind turbine performance comparison involving a two-stage Savonius rotor with similar parameters. The experimental study is conducted in the aerodynamic tunnel at the Fluid Mechanics Laboratory of the Federal University of Rio Grande do Sul. The aerodynamics rotors are manufactured by 3D prototyping technique. Numerical simulations are performed using the Finite Volumes Method performed by the solution of the Reynolds Averaged Navier-Stokes (RANS) and continuity equations using the SST k-ω turbulence model. The numerical domain is modeled in order to maintain the same characteristics of the experimental model. The mesh quality is evaluated through the GCI (Grid Convergence Index) method. The static and dynamic torque coefficients and the power coefficients are compared. The tests are made without blockage corrections due to the small blockage ratio from 7.5%. Results show that the turbine has a positive static torque coefficient for any rotor angles. The dynamic torque reaches the maximum value for a tip speed ratio (λ) of 0.2 for the experimental and numerical cases. The relative difference between the numerical simulations and the experimental results are between 3.8% and 13.4%.